Circo do Povo: estratégias metodológicas e miscelânea artística, de 1983 a 2019 - Ued, Anderson Gallan (2020)
The reflections proposed in this research are based on the tangles of knowledge that underpinned the dramaturgical constructions, as well as on the pedagogical methodological strategies adopted for the transmission of circus knowledge in Circo do Povo, a sociocultural project of the City of Uberaba, MG, between 1983 and 2019. Through interviews with the instructors who worked or have been working in this circus and through researches in local newspapers of the analyzed period, I point out debates, disputes, trajectories and influences that converged and have been converging to the plurality of artistic expressions of the Circo do Povo. I also point out the ways of constructing the dramaturgies of the shows, which were based on the meetings of generations, the affections, the involvement and the sharing between the reinvented instructors and the students. Thus, I try to demonstrate that this artistic miscellany, pedagogical knowledge and aesthetic options, on the part of the instructors, was decisive for the structuring of dramaturgical creations in the Circo do Povo, sometimes influenced by artists of the traveling circus, sometimes by artists with theatrical training, sometimes by the combination of the two profiles.